Weakly (I, J)-continuous multifunctions and contra (I, J)-continuous multifunctions (2019)
The purpose of the present paper is to introduce, study and characterize upper and lower weakly (I, J)-continuous multifunctions and contra (I, J)-continuous multifunctions. Also, we investigate its relation with another class of continuous multifunctions. AMS Subject Classification: 54C10, 54C08, 54C05, 54C60